2022
DOI: 10.1021/acs.jafc.1c07358
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA Profiling Identifies Novel circPPARA that Promotes Intramuscular Fat Deposition in Pigs

Abstract: Intramuscular fat (IMF) content plays an important role in pork quality. Circular RNAs (circRNAs) implicate various biological processes; however, the regulatory mechanisms and functions of circRNAs in porcine IMF remains elusive. Hence, the study assessed the circRNA expression profiling in the longissimus dorsi muscle of pigs with high (H) and low (L) IMF content to unravel their regulatory functions in improving meat quality. The RNA sequencing analysis identified 29,732 circRNAs from six sampled pigs, most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 67 publications
1
26
0
Order By: Relevance
“…Further analysis showed that the circRNAs identified were mainly generated by cyclization of gene exons ( Zhang M. L. et al, 2018 ), in the sheep ( Lv et al, 2020 ) and cattle ( Liu et al, 2020 ), indicating similar origins of circRNAs in different species. In our present study, we found that the majority of circRNAs are less than 10,000 nt in length, which is consistent with the results of a previous study in goat ovary ( Liu et al, 2022 ), but longer than circRNAs identified in goat endometrial ( Li et al, 2022 ), indicating that the longer the sequence, the greater the corresponding increase in the difficulty of circRNA loop formation. Moreover, most of the identified circRNAs were typically distributed on chromosomes 1-11, and the expression of circRNAs in the luteal phase was more abundant than that in the follicular phase of the oviduct, indicating that the functions of circRNAs in the oviduct are diverse.…”
Section: Discussionsupporting
confidence: 93%
“…Further analysis showed that the circRNAs identified were mainly generated by cyclization of gene exons ( Zhang M. L. et al, 2018 ), in the sheep ( Lv et al, 2020 ) and cattle ( Liu et al, 2020 ), indicating similar origins of circRNAs in different species. In our present study, we found that the majority of circRNAs are less than 10,000 nt in length, which is consistent with the results of a previous study in goat ovary ( Liu et al, 2022 ), but longer than circRNAs identified in goat endometrial ( Li et al, 2022 ), indicating that the longer the sequence, the greater the corresponding increase in the difficulty of circRNA loop formation. Moreover, most of the identified circRNAs were typically distributed on chromosomes 1-11, and the expression of circRNAs in the luteal phase was more abundant than that in the follicular phase of the oviduct, indicating that the functions of circRNAs in the oviduct are diverse.…”
Section: Discussionsupporting
confidence: 93%
“…The calculation formula was as follows: SRPBM = (Back spliced junction reads / Total number of mapped reads)×10 9 .…”
Section: Quality Control For Raw Reads and Circrna Identi Cationmentioning
confidence: 99%
“…As a polygenic trait, IMF is a complex metabolic process determined by the hyperplasia and hypertrophy of adipocytes and involves many biological processes and pathways, which are regulated by various molecules, such as hormones, transcription factors, protein-coding genes, and non-coding RNAs [ 10 , 11 , 12 ]. However, when compared with other traits, dissecting the genetic basis of IMF content is still limited, owing to its complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Further, LMFlnc1 (lncRNA) promotes adipogenesis in porcine IMF cells by upregulating CAV-1 expression via miR-199a-5p [ 14 ]. Moreover, Sus_circPPARA promotes differentiation and hinders proliferation in porcine intramuscular preadipocytes [ 11 ]. Despite the increasing number of transcriptomic studies aimed at dissecting IMF deposition, cascade events related to this trait remain mostly unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation